2021
DOI: 10.31234/osf.io/n8tm7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Correlates of Mental Health Support Access Among Sexual Minority Youth of Color During COVID-19

Abstract: Objective: Many youth with mental health needs cannot access treatment, with multiply-marginalized youth, such as sexual minority youth of Color (SMYoC), experiencing both structural and identity-related barriers to care. The COVID-19 pandemic threatens to exacerbate multi-level treatment access barriers facing SMYoC youth nationwide. However, little large-scale research has examined access to mental health care among SMYoC across the United States, either during or prior to the pandemic. Such work is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Many children have undergone the trauma of losing a loved one to COVID‐19 and may experience symptoms of grief, exacerbating psychological and physical symptoms of PASC. Additionally, the pandemic has exacerbated difficulty with access to mental health care for many populations such as racial and ethnic minority groups and gender/sexual minority individuals 56 . One study demonstrated that children, girls, those with Hispanic ethnicity, those with public versus private insurance, and those with more significant medical comorbidity were more likely to exhibit PASC neuropsychiatric symptoms, 57 although these demographic and socioeconomic factors need to be studied further.…”
Section: Initial Evaluation Of Children and Adolescents With Pascmentioning
confidence: 99%
See 1 more Smart Citation
“…Many children have undergone the trauma of losing a loved one to COVID‐19 and may experience symptoms of grief, exacerbating psychological and physical symptoms of PASC. Additionally, the pandemic has exacerbated difficulty with access to mental health care for many populations such as racial and ethnic minority groups and gender/sexual minority individuals 56 . One study demonstrated that children, girls, those with Hispanic ethnicity, those with public versus private insurance, and those with more significant medical comorbidity were more likely to exhibit PASC neuropsychiatric symptoms, 57 although these demographic and socioeconomic factors need to be studied further.…”
Section: Initial Evaluation Of Children and Adolescents With Pascmentioning
confidence: 99%
“…Additionally, the pandemic has exacerbated difficulty with access to mental health care for many populations such as racial and ethnic minority groups and gender/sexual minority individuals. 56 One study demonstrated that children, girls, those with Hispanic ethnicity, those with public versus private insurance, and those with more significant medical comorbidity were more likely to exhibit PASC neuropsychiatric symptoms, 57 although these demographic and socioeconomic factors need to be studied further. With the increase in mental health problems since the start of the pandemic it is particularly important to screen for mental health symptoms in all youth with PASC, and in particular, screen for suicidal ideation especially if there are known past attempts, past suicidal ideation, or changes in mood.…”
Section: Mental Health and Psychiatric Symptomsmentioning
confidence: 99%
“…A. Price, Weisz, et al, 2022) and access (Hollinsaid et al, 2022;Roulston et al, 2022) for stigmatized youth (see Figure 1). The present paper provides a brief overview of the scientific literature on structural stigma and youth mental health treatment, and details three future research directions we hope readers pursue.…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%
“…A. Price, Weisz, et al, 2022) and access (Hollinsaid et al, 2022;Roulston et al, 2022) for stigmatized youth (see Figure 1). The present paper provides a brief overview of the scientific literature on structural stigma and youth mental health treatment, and details three future research directions we hope readers pursue.…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%